Analisis Keberlanjutan Sistem Agroforestri Tradisional Di Desa Salua Kecamatan Kulawi Kabupaten Sigi Sulawesi Tengah - Ferianto Ferianto; Arief Sudhartono; Sri Ningsih (Universitas Tadulako, 2017)
The research aims were to identify the biophysical condition of agroforestry land in Salua Village, to analyze the socio-economic and community institution condition in Salua Village, and to analyze the sustainability of agroforestry system perceived from the aspects of land biophysical condition, socio-economic and community institution condition in Salua Village. This research was an explorative-descriptive study done through survey method. Data collected was by interviewing respondents and by direct observation and measurement in the field. The number of respondents was 30 people included village government officer, members of traditional institutions and farmer groups who live in Salua village. The tool of analysis consisted of vegetation analysis, soil analysis, socio-economic analysis, institutional analysis and sustainability analysis using Likert scale of 1,3 and 5. The soil analysis indicated that soil nutrient contents were still very good for supporting plant growth. The socio-economic condition was dependent upon land tenure, profit-sharing system, and area size of tilled land and plant types. Increasing production is strongly needed by the farmers. The four dimension aggregate index showed that the average value was 50% for the socio-economic dimension, 66.7% for the ecology, 60%for the production and 100% for the institution. Based on the analysis on vegetation, socio-economy, institution and sustainability using Likert scale, it can be concluded that the condition of agroforestry land in Salua village tend to be sustained.